2005
DOI: 10.4049/jimmunol.174.4.2327
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Autoimmune Retinal Disease by Lovastatin Does Not Require Th2 Cytokine Induction

Abstract: Intraocular inflammatory diseases are a common cause of severe visual impairment and blindness. In an acute mouse model of autoimmune retinal disease, we demonstrate that treatment with the HMG-CoA reductase inhibitor, lovastatin, suppresses clinical ocular pathology, retinal vascular leakage and leukocytic infiltration into the retina. Efficacy was reversed by co-administration of mevalonolactone, the downstream product of HMG-CoA reductase, but not by squalene which is distal to isoprenoid pyrophosphate meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…Most studies relating to the immunomodulatory properties of statins in autoimmunity have studied their effects on animal models of disease with a predominant Th1-driven response (2,3). However, induction of a Th2 cytokine response by statins has not been a universal feature in rodent models of autoimmune disease (48) or in human primary PBMC from patients with multiple sclerosis, where an in vitro study observed an increase in IFN-␥ and reduction in IL-10 production (49). Th1 and Th2 cytokines both contribute to the pathogenesis of lupus disease, which is not so easily defined within the classical Th1/Th2 paradigm (50).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies relating to the immunomodulatory properties of statins in autoimmunity have studied their effects on animal models of disease with a predominant Th1-driven response (2,3). However, induction of a Th2 cytokine response by statins has not been a universal feature in rodent models of autoimmune disease (48) or in human primary PBMC from patients with multiple sclerosis, where an in vitro study observed an increase in IFN-␥ and reduction in IL-10 production (49). Th1 and Th2 cytokines both contribute to the pathogenesis of lupus disease, which is not so easily defined within the classical Th1/Th2 paradigm (50).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was reversed with mevalonate but not with squalene, suggesting an action on one or more prenylated proteins. The cell type(s) through which lovastatin mediated this effect is unclear, but lovastatin significantly suppressed in vitro transendothelial migration of mouse lymphocytes; lymphocyte transmigration was restored with the addition of mevalonate (124).…”
Section: Abeles and Pillingermentioning
confidence: 99%
“…This activity highlights statins as potential drugs in the treatment of diseases dominated by Th1 responses. Statins have been indeed shown to prevent or reverse several Th1-mediated autoimmune conditions in mice, such as autoimmune encephalomyelitis [8], spontaneous systemic lupus erythematosus [9,10], autoimmune myocarditis [11] and autoimmune retinal disease [12] via suppression of Th1-type cytokine secretion through a mechanism involving primarily their inhibitory effects on isoprenoid biosynthesis [7,12]. Conversely, atorvastatin does not appear to affect the Th1/Th2 balance either in an experimental autoimmune uveitis mouse model [13] or in autoimmune diabetes in NOD mice [14].…”
mentioning
confidence: 99%